Autoinflammatory diseases. Part 2. Pyrin inflammasomopathies and other enhanced interleukin 1 signaling syndromes - О.В. Шварацька; Т.А. Бордій; К.К. Годяцька; М.В. Калічевська; О.В. Клименко; О.М. Таран; О.В. Клімова; Я.В. Віленський (Zdorovʹe Rebenka, 2024)
Systemic autoinflammatory diseases (SAIDs) are considered dysregulation disorders of the innate immune system characterized by systemic sterile inflammation independent of infection and autoreactive antibodies or antigen-specific T cells. Autoinflammation is often mediated by inflammasomes; accordingly, inflammasomopathies and other enhanced interleukin (IL) 1 signaling syndromes represent a major classification group of SAIDs. Inflammasomes differ by the type of intracellular receptor which acts as a scaffold protein for the entire complex. Specifically, pyrin is one of the main intracellular sensor proteins that can initiate the formation of inflammasomes. This scientific review is the second in a series of publications jointly aiming to increase medical professionals’ awareness of SAIDs in children. It focuses on the current scientific understanding of pyrin inflammasomopathies which represent a significant cluster of all inflammasomopathies and other enhanced IL-1 signaling syndromes. We performed a focused search over the Web of Science, Scopus, PubMed Central®, Google Scholar databases over the past 10 years using the keywords “autoinflammatory diseases”, “autoinflammation”, “inflammasomopathies”, “pyrin”. The work presents an overview of inflammasomopathies, discusses the immunobiological features of the sensor protein pyrin and pyrin inflammasomes including cellular expression and molecular mechanisms of their activation and signal limitation. The review also presents the clinical and pathogenetic characteristics of the genetically determined pyrin inflammasomopathies and other enhanced IL-1 signaling syndromes: familial Mediterranean fever; pyrin-associated autoinflammation with neutrophilic dermatosis; mevalonate kinase deficiency; PSTPIP1-associated inflammatory diseases; periodic fever, immunodeficiency and thrombocytopenia syndrome; neonatal-onset cytopenia with dyshematopoiesis, autoinflammation, rash, and hemophagocytic lymphohistiocytosis; deficiency of IL-1 receptor antagonist; deficiency of IL-36 receptor antagonist; loss of IL-1 receptor to IL-1 receptor antagonist syndrome.